Juridical Analysis of Confiscation of Looted Goods and State Seizures in Corruption Crimes - Nur Kevin Kaluku (Universitas Negeri Gorontalo, 2019)
Abstract:The act of confiscation of goods resulting from criminal acts of corruption is not easy and faces various obstacles in its implementation. The existence of confiscated and confiscated objects that have expensive maintenance costs has actually become a new burden for the government and has the potential to pose a big risk in the future. The purpose of this research is to examine the procedures for confiscation of confiscated goods and state confiscations in corruption crimes as well as to formulate efforts that will optimize the regulation of confiscated goods and state confiscations resulting from criminal acts of corruption. This research is a normative research using a law approach, a case approach, and a conceptual approach in the research approach. The results of the study indicate that the existing problem is that the procedure for confiscation of confiscated goods and state confiscations resulting from criminal acts of corruption is carried out and involves various agencies, namely the Attorney General's Office, the Corruption Eradication Commission (KPK), the Ministry and Rupbasan in accordance with the legislation that has been set. However, in practice there are various obstacles that must be improved and minimized by the various agencies. With regard to confiscated and confiscated goods, criminal acts of corruption use the in personam principle Keywords: Corruption, Confiscation, Looted Goods